Abuse of authority in the State of Emergency due to the (Covid-19) pandemic in Peru, from the perspective of Critical Criminology. - Manuel Yeferson Grando Mamani (2021)
The fact that a person has a public position, whether police or military, etc., does not have the power, much less the power to act in violation of the law, that is, not respecting the protocols and exceeding the use of the law. strength that the state confers on them; Although the abuse of authority is true, prescribed in the Penal Code, it supposes a criminal policy orientation aimed at closing spaces of impunity when the conduct attributed to the public official does not comply with the regulatory scope. For this reason, it is born from this flaw to analyze the abuse of authority from the perspective of Critical Criminology, where the inefficiency of the State against the measures and regulation of the abuse of authority is refuted, the main objective of the work being to identify what abuse of authority is caused and within the specific objectives, describe and explain the misuse of force by executive agents within the state of emergency by (Covid-19) in Peru, finally it is shown that there is an excessive use of force by law enforcement agents and inefficiency of state bodies in the face of this conflict.